When Palpitations and Hand Weakness Point to the Aorta: An Atypical Case of Aortic Dissection - Admire Hlupeni; Andrew Nunno; Manirul Tamal; Jeffrey Murray (Annals of Internal Medicine: Clinical Cases)
Aortic dissection (AD) is a life-threatening condition often presenting with varied symptoms, complicating early diagnosis. We present a case of a 58-year-old woman with untreated hypertension and a remote history of cardiac ablation who presented with persistent palpitations and transient left-hand weakness, but without chest or back pain. An incidental AD was identified during imaging for a suspected transient ischemic attack. Effective blood pressure management and prompt cardiothoracic intervention, with successful surgical repair, enabled favorable outcomes. This case underscores the diagnostic challenges posed by atypical AD presentations, highlighting the importance of maintaining high index of suspicion in at-risk population.